HUBUNGAN PENGETAHUAN DAN SIKAP IBU NIFAS TENTANG TEKNIK MENYUSUI YANG BENAR DI KLINIK JULIANA DALIMUNTHE MEDAN TAHUN 2022 - KAMALIAH .; ELVI SEPRIANI (JURNAL ILMIAH KOHESI, 2022)
Breastfeeding is an activity that can bring happiness to the mother, which is her nature. To support the success of breastfeeding, it is necessary to know the correct breastfeeding technique. Breastfeeding with improper technique can result in sore nipples. The research design on “The Relationship between Knowledge and Attitude of Postpartum Mothers About Correct Breastfeeding Techniques at the Juliana Dlimunthe Clinic Medan in 2022 is descriptive in the form of observation and the approach used is Cross Sectional. The population in this study were all postpartum mothers who gave birth at the Juliana Dalimunthe Clinic, Medan as many as 30 respondents. The sample in this study was using total sampling, namely all postpartum mothers who gave birth at the Juliana Dalimunthe Clinic, Medan, namely 30 respondents. From the results of the study obtained from 30 respondents, the majority who have sufficient knowledge about the correct breastfeeding technique are 14 respondents (46.7%). And the minority with good knowledge are 7 respondents (23.3%) while the attitude of postpartum mothers about the correct breastfeeding technique mostly has a positive attitude as many as 19 respondents (63.3%), while those who have a negative attitude are 11 respondents (36.7% ). Based on the calculation of the Chi-Square test analysis, it is known that the significant p value is 0.004. Because the p value is smaller than 0.05 (0.004 <0.05), the hypothesis is accepted so that in this study there is a significant relationship between knowledge and attitudes of postpartum mothers about correct breastfeeding techniques at the Juliana Dalimunthe Clinic, Medan in 2022.